Locally advanced adenocarcinoma of the rectum presenting with necrotising fasciitis of the perineum: successful management with early aggressive surgery and multimodal therapy - Ferreira, L (2015)
Colorectal cancer is a common malignant neoplasm and its treatment usually involves surgery associated, in some cases, depending on the staging, with chemoradiotherapy. Necrotising fasciitis of the perineum is a highly lethal infection of the perineum, perirectal tissues and genitals, requiring emergency surgical debridement, broad-spectrum antibiotics and control of sepsis. We present the case of a 59-year-old man with necrotising fasciitis of the perineum as the first clinical manifestation of locally advanced adenocarcinoma of the rectum, in which successful management consisted of early and aggressive surgical debridement, followed by multimodal therapy with curative intent. 2 years and 6 months after surgery the patient is well, with no evidence of local or systemic relapse.